Anticipating a MERS-like coronavirus as a potential pandemic threat - Zumla, Alimuddin; Peiris, Malik; Memish, Ziad A; Perlman, Stanley (The Lancet (British edition), 2024)
[...]since merbecoviruses occur worldwide, increased attention and investments are needed for human, camel, and bat research to enable the rapid development of diagnostics, vaccines, and antivirals if a merbecovirus-mediated human disease is identified. [...]improved understanding of why some coronaviruses robustly infect the human upper airway, facilitating transmission in pre-symptomatic and early symptomatic disease, whereas others (eg, SARS-CoV) that also use the ACE2 receptor do not will be important to identify merbecoviruses with pandemic potential. Predicting the future evolutionary trajectory of MERS-CoV, MERS-like coronaviruses, and other coronaviruses remains important for public health planning and will require substantial financial investments. Since Saudi Arabia and Arabian Gulf countries have been grappling with Middle East respiratory syndrome for the past decade, they are in a strong position to take leadership of the portfolio of defined research and development priorities.